Telemedicine-Guided Stroke Thrombolysis in a COVID-19 Patient Admitted in a Field Hospital - Accorsi, Tarso A. D.; Brigido, Alexandra R. D.; Habrum, Fabio C.; Carvalho, Flavio A. de; Lima, Karine De Amicis; Pedrotti, Carlos H. S.; Cordioli, Eduardo (Archives of Clinical and Medical Case Reports, 2020)
Telemedicine might be crucial during the current pandemic, helping in re-structuring the health system. This paper is a case report of a COVID-19 patient admitted to a field hospital who presented an infection-triggered ischemic stroke. She was examined by allocated general practitioners and had a life-threatening situation. The correct application of treatment guidelines is a challenge in this scenario and the feasibility of telemedicine-guided treatment is still uncertain. This report aims to demonstrate the effectiveness of teleconsultation in an emergency. There was a retrospective data compilation from the patient's medical record and subsequent exposure of the main findings. The patient presented typical viral pneumonitis on chest CT scan, she was on supportive treatment and presented acute neurological deficit on the tenth day after respiratory manifestation. Immediate skull CT scan did not show blood and there was stippling in sylvian branches of a left middle cerebral artery. There was telemedicine-guided confirmation of the diagnosis, tomographic interpretation, decision-making, and thrombolytic administration. There is a demonstration of the feasibility of teleconsultation in a time-effective manner, reinforcing the need to expand the telemedicine program in multiple scenarios.